Emphysematous gastritis associated with ileus due to fecal impaction. Issue 1 (8th June 2022) - Takada, Ryuji; Nagasawa, Hiroki; Yanagawa, Youichi
Abstract: Background: Gastric emphysema and emphysematous gastritis (EG) are rare diseases involving air being introduced into the stomach wall. Emphysematous gastritis is an infectious disease with a high fatality rate. Case presentation: An 83‐year‐old woman had recovered from septic shock, however, an antibiotic‐refractory inflammatory response remained. She was diagnosed with pseudogout and administered a non‐steroidal anti‐inflammatory drug. However, abdominal pain, prominent abdominal distension, and strawberry milk‐like gastric juice were recognized. Computed tomography showed ileus due to fecal impaction and GE. The results of culture of the gastric juice were positive ( Pseudomonas aeruginosa and Enterococcus faecalis ). Disimpaction, fasting management, and antibacterial treatments resulted in the recovery of her symptoms. Conclusion: This is the first case in which ileus associated with fecal impaction caused EG. The present case highlights the importance of promoting regular bowel movements. Abstract : This is the first case in which ileus due to fecal impaction caused emphysematous gastritis. The present case highlights the importance of promoting regular bowel movements.